Pseudosetipinna Peng & Zhao is a junior synonym of Setipinna Swainson and Pseudosetipinna haizhouensis Peng & Zhao is a junior synonym of Setipinna tenuifilis (Valenciennes) (Teleostei: Clupeoidei: Engraulidae) - Lavoué, Sébastien; Ho, Hsuan-Ching (Zootaxa, 2017)
The validity of Pseudosetipinna Peng & Zhao and its type and only species, Pseudosetipinna haizhouensis Peng & Zhao, has long been doubtful due to the absence of diagnostic characters other than the lack of pelvic fins. The absence of pelvic fins in specimens of anchovies and sardines is frequently reported and usually considered a developmental malformation. We recently collected specimens of S. tenuifilis (Valenciennes) containing one specimen without pelvic fins, identifiable as P. haizhouensis. Herein, we conducted detailed morphological and genetic analyses to determine the validity of P. haizhouensis. The morphological results confirmed that the absence of pelvic fins allows the distinction between P. haizhouensis and S. tenuifilis. The genetic results showed that the mitochondrial haplotype of P. haizhouensis is shared with S. tenuifilis. Altogether, the evidence suggests that P. haizhouensis and S. tenuifilis belong to the same species. Consequently, Pseudosetipinna is a junior synonym of Setipinna Swainson and P. haizhouensis is a junior synonym of S. tenuifilis.